The Development of Crypto Legislation in Europe - Halász Zsolt (HUNGARIAN YEARBOOK OF INTERNATIONAL LAW AND EUROPEAN LAW, 2024)
Experience with the issuance of crypto-assets and crypto-asset-related services over the last decade and a half shows that the diversity and complexity of services and, not least, the necessity to protect the interests of users, require regulation of both the creation (issuance) and the provision of services related to crypto-assets. In Europe, regulatory attempts have been made in several states, but the global usability of cryptoassets requires comprehensive, transnational regulatory solutions. Although such a global regulatory response is not yet in place, at least the foundations have been laid in the EU. EU regulation is an important step forward because it will at least allow the issuance of cryptoassets and the provision of cryptoasset services in all EU Member States to operate under the same rules. The creation of EU regulation could also serve as a global regulatory model. The protection of customers and consumers is a particularly essential element of the regulation, some elements of which are already covered by the EU MiCA Regulation, but the customer and consumer protection needs to be further strengthened.